PENGGUNAAN METODE CERAMAH DAN DISKUSI UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA PELAJARAN FIKIH SISWA KELAS VII MTSN 15 JOMBANG: METODE CERAMAH DAN DISKUSI UNTUK MENINGKATKAN PEMAHAMAN SISWA - Sofiani Hanjani; Falah, Moh. Syamsul; Mas'ud (PAI FAI UNHASY Tebuireng Jombang, 2025)
Abstract : Learning is an activity that involves a process for individuals to achieve behavioral changes through experiences from interactions with their environment. This research aims to improve learning outcomes in fiqh subjects at MTsN 15 Jombang by applying direct lecture and group discussion methods. The research subjects were teachers who used discussion and lecture learning models. This research uses a qualitative approach and observation methods. Data was collected from interviews with fiqh subject teachers and observations at MTsN 15 Jombang. The data analysis techniques applied include data reduction, data presentation, verification and drawing conclusions.